Estrategias para la prevención de bullying cibernético en la Unidad Educativa Sagrado Corazón de Jesús. - Pazmiño Torres, Cristina Jessenia (2023)
The Internet is a space in which each of us has created an imaginary life, but the misuse of social networks can lead to poor digital communication; in this context, cyberbullying has stood out since 2004. Within educational institutions it has been observed that students also present this aggressive behavior on the internet, by making some kind of "jokes" that become offensive or even harassing against some of their peers, turning this into cyberbullying, a problem previously referred to only as bullying because no digital media was used for this; of this situation was born the initiative to make the present study to students of the third year of baccalaureate of the Sacred Heart of Jesus Educational Unit of the city of Latacunga province of Cotopaxi, to create some digital communication strategies that were practiced to prevent cyberbullying in this group of students. For the development of this project the exploratory - descriptive method was used, since there was no previous study of the subject within the institution and the research could be analyzed directly, some of the strategies created are: Establish safe spaces with professionals experts in the area of psychology and legal, so that students can identify patterns or behaviors that are considered cyberbullying, work with students to design posters, audiovisual and talks that were disseminated within the educational community and in the social networks of the institution.